1992
DOI: 10.1093/ije/21.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Trachoma in Bebedouro State of São Paulo, Brazil: Prevalence and Risk Factors

Abstract: Trachoma was considered to have been 'eradicated' from the state of São Paulo, Brazil, until 1982 when a number of new cases of trachoma were reported in preschool children in Bebedouro, a small town in northwestern São Paulo. A household survey was undertaken to assess the prevalence and epidemiological characteristics of trachoma. A total of 2939 people of all ages was examined having been selected from a two-stage probalilistic household sampling frame based on census data. Overall, 7.2% of the population h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
19

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 0 publications
1
34
1
19
Order By: Relevance
“…Trachoma still occurs more frequently in populations in rural areas, concurring with national and international literature. 3,4,8,19 There was no difference with regards to the distribution of cases by sex, which is consistent with data reported in Brazilian studies of schoolchildren. 1,2,5,10,11 Distribution according to sex in Brazil differs from other countries, where higher prevalence among females has been observed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Trachoma still occurs more frequently in populations in rural areas, concurring with national and international literature. 3,4,8,19 There was no difference with regards to the distribution of cases by sex, which is consistent with data reported in Brazilian studies of schoolchildren. 1,2,5,10,11 Distribution according to sex in Brazil differs from other countries, where higher prevalence among females has been observed.…”
Section: Discussionsupporting
confidence: 89%
“…4 However, various studies realized after the mid 1980s, in different regions and states, found prevalence varying between 1.5% and 47.7% for active trachoma and from 0.1% to 2.0% for trichiasis, including indigenous populations. 1,2,[5][6][7][8]11,12,14,15 The WHO considers trachoma to be a neglected disease. According to its criteria for eliminating the disease as a cause of blindness, the prevalence of trachomatous infl ammation -follicular needs to be reduced to under 5% in children aged from one to nine, and prevalence of trachomatous trichiasis to less than one case per thousand inhabitants in a community or district.…”
mentioning
confidence: 99%
“…No entanto, sua presença volta a ser assinalada nos anos 80, mas com baixa endemicidade. Luna et al 5 verificaram na região noroeste do Estado de São Paulo prevalência de 2,1% da forma inflamatória do tracoma, atingindo principalmente as populações rurais e periurbanas.Poucos estudos têm detalhado o comportamento do tracoma em áreas hipoendêmicas. As publicações focalizando a região metropolitana de São Paulo sugerem uma baixa prevalên-cia, porém os estudos não foram conclusivos quanto aos principais fatores de risco, tornan-…”
unclassified
“…4,15 Higher susceptibility to trachoma is generally associated with poor water supply and poor sanitation and housing conditions and thus this disease is an indicator of poverty and underdevelopment. 4,6,15 In endemic areas, the prevalence of inflammatory trachoma tend to decrease with age while its sequelae, such as scarring, trichiasis, and corneal opacity, increase with age. 4,11,15 Endemic trachoma can be seen in many regions of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southeastern state of São Paulo, prevalences are lower than in Northeastern states. 5,6,11,14 Trachoma reemerged in the city of São Paulo in 1990 and this led to an intervention in epidemiological surveillance. Studies carried out in the 1990's in the city of São Paulo showed disease prevalences ranging from 2.8% in Freguesia do Ó district to 4.7% in Bela Vista district.…”
Section: Introductionmentioning
confidence: 99%